Pécs egyházi kincseinek sorsa a 16. század második felében - Varga, Szabolcs (Per Aspera ad Astra, 2015)
The study reveals the fate of the medieval treasures of the cathedral of Pécs. The majority of these religious objects disappeared after the Ottoman conquest, and nothing was known about them for a long time. However, some sources help historians reconstruct the survival of some of them. The study shows that several treasures were taken to Bratislava where they were guarded by the bishop and canons of Pécs. András Dudich, Bishop of Pécs pawned many of the treasures in the 1560s. Miklós Telegdy attempted to find them in the 1570s, but his efforts proved to be fruitless; he only managed to find only a few of them, while the treasures vanished again from our sources in the 17th century. Therefore, their latter fate can only be guessed.